Singin' in the rain - Brown, Nacio Herb 1896-1964 (Warner Bros. Home Entertainment, 2022)
Silent movies are giving way to talking pictures, and a hoofer-turned-matinee idol is caught in that bumpy transition, as are his buddy, prospective ladylove, and shrewish costar
Suggested by the song "Singin' in the rain.
Originally released as a motion picture in 1952
Full screen (1.37:1)
Special features: commentary by Debbie Reynolds, Donald O'Connor, Cyd Charisse, Kathleen Freeman, Stanley Donen, Betty Comden, Adolph Green, Baz Luhrmann and Rudy Behlmer; jump-to-song feature; (Blu-ray only): Singin in the rain: Raining on a new generation; theatrical trailer
Keywords: Motion picture industry / Drama; Dancers / Drama; Man-woman relationships / Drama; Dancers; Man-woman relationships; Motion picture industry; Drama; Feature films; Fiction films; Musical films; Show business films; Video recordings for the hearing impaired; Film; Blu-Ray-Disc; Ultra HD Blu-ray